A memory-recall checklist for dental services during the COVID-19 outbreak: A clinical recommendation - Amal A Al-Khotani; Haila A Al-Huraishi; Dalia E Meisha (Wolters Kluwer Medknow Publications, 2020)
The epidemic coronavirus disease 2019 (COVID-19) has infected millions of people and put a huge amount of stress on the health-care system. Health-care professionals, including dental professionals, are at a high risk of acquiring COVID-19. Therefore, extra precautions need to be implemented for routine dental infection control procedures. It is encouraged to have a written reminder in the form of a checklist to recall these crucial steps, especially when nonroutine procedures must be followed. The aim of this special communication is to present a proposed mnemonic or memory-recall, user-friendly checklist to be used in the dental clinic during the COVID-19 outbreak. The checklist was created following the guidelines for reopening dental services in governmental and private sectors during the COVID-19 pandemic that were published by the Ministry of Health on June 5, 2020. Based on the patient's score and the urgency of the dental situation, specific steps should be followed. When the patient's score is ≥ 4 and needs an emergency aerosol-generating procedure, REDS steps should be recalled. Further, MRS steps must be followed if the patient's score is < 4. For both groups, GAMES can be followed when personal protective equipment is needed before the patient examination and HD steps should be applied after finishing the dental procedure. In conclusion, this written reminder in the form of a checklist can be helpful for a safe dental practice during pandemics to recall the crucial nonroutine steps. We recommend that the dental staff place those steps as a written reminder in an accessible, visible place.